2002
DOI: 10.1590/s0104-11692002000100011
|View full text |Cite
|
Sign up to set email alerts
|

Sexualidade do portador do vírus da imunodeficiência humana (HIV): um estudo com base na teoria da crise

Abstract: A investigação teve como objetivo identificar e analisar as dificuldades sexuais e as suas inter-relações com as dificuldades sociais e emocionais vivenciadas por sujeitos em crise de HIV. Os dados foram coletados através de entrevista semi-estruturada, gravada, e após, foram transcritos, categorizados e analisados. Elaboramos a transcrição das falas gravadas, e através da utilização da análise temática, criamos cinco histórias com o título: ..."O viver com HIV". Na análise dos dados a interpretação do conteúd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 1 publication
0
7
0
7
Order By: Relevance
“…When people discover they are HIV-infected, many isolate themselves due to fear of rejection and abandonment, when they think of disclosing their serostatus 1,2,3,4 . Studies on the issue with samples of persons living with HIV in countries of the Americas, Europe, and Asia with access to treatment have indicated that disclosing one's HIV diagnosis decreases stress and isolation, expands social support, and favors adaptation to medication intake and negotiation of safer sex in various inter-subjective contexts, with an impact on controlling the spread of the epidemic.…”
mentioning
confidence: 99%
“…When people discover they are HIV-infected, many isolate themselves due to fear of rejection and abandonment, when they think of disclosing their serostatus 1,2,3,4 . Studies on the issue with samples of persons living with HIV in countries of the Americas, Europe, and Asia with access to treatment have indicated that disclosing one's HIV diagnosis decreases stress and isolation, expands social support, and favors adaptation to medication intake and negotiation of safer sex in various inter-subjective contexts, with an impact on controlling the spread of the epidemic.…”
mentioning
confidence: 99%
“…Out of the 14 studies analyzed, seven used a qualitative approach (4,6,(8)(9)11,(18)(19) , five were quanti-qualitative (7,(12)(13)15,20) and two studies were quantitative (5,14) .…”
Section: • First Aspect: Methodological Approachesmentioning
confidence: 99%
“…It was identified that the theoretical frameworks used come from the human sciences, such as social psychology, psychoanalysis and sociology, and these were: Theory of crisis and process of solving problems (18) ; Stressful events (13) ; Ways of coping with problems (15,20) ; Mechanisms of defense (9) ; Post-structuralist perspective of the cultural studies, supported in the contributions of Michel Foucault -using the allegory of the blanket (19) and Sexuality (6) . The second approach refers to gender issues, especially regarding women's vulnerability in relation to HIV transmission and falling ill from AIDS.…”
Section: • Second Aspect: the Theories That Support The Discoursementioning
confidence: 99%
“…Six papers (19)(20)(21)(22)(23)(24) were identified in this thematic group and even though they were published in a time when a sweeping debate was taking place on the feminization of AIDS, only one addresses the issue of gender vulnerability (20) . The authors indicate the need for new approaches in nursing in relation to AIDS, in which gender and sexuality are present.…”
Section: Sexuality and Sti/aidsmentioning
confidence: 99%
“…In studies that included both men and women in the studied population (22)(23) , it was difficult to identify to what "subjects" the authors were referring, men or women.…”
Section: Sexuality and Sti/aidsmentioning
confidence: 99%